GNSS Ambiguity Resolution for Attitude Determination: Theory and Method. - Teunissen, Peter (Curran Associates, 2008)
In this contribution we give a brief review of the integerleast-squares theory for GNSS attitude determination, togetherwith a description of the key elements that makeup the LAMBDA method for resolving the baseline constrainedinteger ambiguities.